Volume Analysis of Mining Excavation Progress Using Unmanned Aerial Vehicle-Photogrammetry Method - Susilo, Helik; Rahardion, Aqil; Bani, Martince Novianti; Cupasindi, Dyah Ayu Rahmawati; Aditya, Muhammad Tri; Asema, Fuji; Anggraini, Novita (CIVED, 2024)
In recent years, the use of unmanned aerial vehicles (UAVs) has become an alternative for topographic mapping, and this is called the UAV-Photogrammetry method. Topographic mapping in mining activities is carried out to determine the progress of actual volume of material taken. However, in general, topographic mapping is carried out using terrestrial survey methods. These methods require a long data acquisition time and a lot of personnel. This paper focuses on surveying the volume of mining progress using the UAV-Photogrammetry method and compares it with truck count volume data. The results of this study showed that the deviation in volume calculations using UAV-Photogrammetry method compared with truck count volume data in week I was 233 m3 or 0.654%, week II was 214 m3 or 0.151%, week III was 496 m3 or 0.840%, and week IV was 243 m3 or 0.210%. The results of the t-test showed that there was no significant difference between the volume calculation using the UAV-Photogrammetry method and truck count data, which means both measurement types produce statistically similar results.